All Days 2016
DOI: 10.2118/180386-ms
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Low Salinity Water Flooding and Preformed Particle Gel to Enhance Oil Recovery for Fractured Carbonate Reservoirs

Abstract: The recovery of oil from carbonate reservoirs is usually low due to their extreme heterogeneity caused by natural fractures and the nature of the oil-wet matrix. Low salinity water flooding (LSWF) and preformed particle gels (PPGs) control conformance are two novel technologies that have recently drawn great interest by the oil industry. We developed a cost-effective, novel, enhanced oil recovery (EOR) technology for carbonate reservoirs by coupling the two technologies into one process. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…On the other hand, incremental oil recovery was ascribed to the decreasing injection water salinity. Alhuraishawy et al (2016) examined several LS water salinities (1, 0.1, and 0.01% NaCl), which produced oil recovery of 34, 40, and 45%, respectively. Brady et al (2015) classify the pH during LS flooding and the effect of low-salinity waterflooding into three categories: (1) pH < 5, because the low positive charge of oil to kaolinite means that the LSW can weaken oil's affinity toward kaolinite; (2) pH 5-6, which is the strongest LS water effect due to the ability of LS water to convert the interactional forces to cause repulsion between oil and kaolinite.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, incremental oil recovery was ascribed to the decreasing injection water salinity. Alhuraishawy et al (2016) examined several LS water salinities (1, 0.1, and 0.01% NaCl), which produced oil recovery of 34, 40, and 45%, respectively. Brady et al (2015) classify the pH during LS flooding and the effect of low-salinity waterflooding into three categories: (1) pH < 5, because the low positive charge of oil to kaolinite means that the LSW can weaken oil's affinity toward kaolinite; (2) pH 5-6, which is the strongest LS water effect due to the ability of LS water to convert the interactional forces to cause repulsion between oil and kaolinite.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the major challenge in the gelant injection process is the uncertainty in its gelation time. The conversion of the gelant into the gel before it reaches target formation or gelant dilution in contact with water fails the gelant performance . Although the gelants have less mechanical strength, PPGs are resistant to all types of saline solutions with high concentrations and have good thermal and mechanical resistance. Therefore, scientific research studies confirmed that the performance of PPGs was more prosperous than that of in situ gels in preventing excess water production from oil reservoirs. …”
Section: Introductionmentioning
confidence: 99%